Tumour infiltrating B cells discriminate checkpoint blockade-induced responses. (December 2022) - Valpione, Sara; Campana, Luca G.; Weightman, John; Salih, Zena; Galvani, Elena; Mundra, Piyushkumar A.; De Rosa, Francesco; Gupta, Avinash; Serra-Bellver, Patricio; Lorigan, Paul; Germetaki, Theodora; Dynowski, Marek; et al.
Abstract: Background: Immune cell-driven anti-cancer activity is paramount for effective responses to checkpoint inhibitors (ICB). However, the contribution of the different immune cell subsets in the circulation and within the tumour is poorly understood. Materials and methods: To elucidate the role of the different cell subsets in anti-tumour responses elicited by ICB, we performed single-cell analysis of the transcriptome and surface proteome of paired pre- and early on-treatment metastatic melanoma tumour biopsies and matched peripheral blood mononuclear cell samples. We next compared the survival of metastatic melanoma patients treated with ICB according to the abundance of pre-treatment tumour-infiltrating B cell clonotypes. Results: We identified cell clusters associated with disease control or progression, defined differential expression of biological pathways likely involved in the immune awakening against the tumour and examined how cell–cell communication patterns between the tumour cell subsets change during treatment. Furthermore, we discovered that B cells (immunoglobulin expression and abundance of B cell clonotypes) discriminate the clinical response after ICB and propose that B cells likely contribute to anti-tumour immunity by antigen presentation through major histocompatibility complex molecules. Finally, we demonstrated that the abundance of tumour-infiltrating B cell clonotypes at baseline identifies two distinct risk groups, a finding that we confirmed in an independent cohort. Conclusions: Our exploratory translational study provides new insights on the mechanistic role of B cells in anti-melanoma immunity during treatment with ICB. Additionally, we support pre-treatment B cell tumour infiltration as a promising prognostic biomarker to be further validated as a tool for clinical risk stratification. Highlights: Pre-treatment tumour infiltrating B cell clonotype abundance discriminate response to ICB (99 characters). B cells likely contribute to anti-tumour immunity by antigen presentation (74 characters). On-treatment B cell gene expression in the tumour-infiltrate identifies responders to ICB (93 characters).